MECHANICAL LOWER LIMB MUSCLE FUNCTION AND ITS ASSOCIATION WITH PERFORMANCE IN ELITE TEAM GYMNASTS - Ole H. Hansen; Lars G. Hvid; Per Aagaard; Kurt Jensen (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
TeamGym (TG) differs from individual gymnastics as it is performed in teams including 6-12 participants competing in acrobatic performance in three disciplines:  trampette jumping, tumbling track jumping, and floor exercises.  The physical demands required by TG athletes largely remain unknown, and likely are dictated by the specific disciplines and equipment used. This study aimed at describing physiological capacity by investigating mechanical lower limb muscle function and its association with TG performance in 24 senior elite (12 males, 12 females) team gymnasts. Methods: Anthropometrical data as well as 25m sprint ability, repetitive jumps (RJ), countermovement jumping (CMJ), drop jumping from a height of 48cm (DJ48), maximal isometric leg press muscle strength (MVC) and rate of force development (RFD) were measured. Results: Significant sex differences (p<0.05) were observed for all variables, except MVC. Total sprint times were 3.36±0.1s in males vs. 3.70±0.1s in females, CMJ height 0.51±0.05 vs. 0.41±0.03m, DJ48 rebound height 0.43±0.06 vs. 0.34±0.06m, with no difference in concentric peak power production between CMJ and DJ48. MVC was 38.3±9.9N/kg in males vs. 36.4±9.2N/kg in females. In female gymnasts, correlations (r2=0.41-0.46, p<0.05) were found between trampette and tumbling performance and sprint ability. In male gymnasts, correlations (r2=0.44, p<0.05) emerged between trampette performance and relative RFD (%MVC/s). Conclusions: Moderate associations were found between mechanical lower limb muscle function and functional tumbling performance in male and female TeamGym, indicating that performance in elite TeamGym also relies on factors other than isolated mechanical muscle function.